Analisis Alokasi Anggaran Pendapatan dan Belanja Daerah dalam Meningkatkan Kesejahteraan Masyarakat di Kabupaten Sidoarjo - Fauzan, Nur Syahwal; Ekyuna, Sheva Arrayan; Fitrie, Revienda Anita; Fanida, Eva Hany (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
<pre id="tw-target-text" class="tw-data-text tw-text-large tw-ta" dir="ltr" tabindex="-1" role="text" data-placeholder="Translation" data-ved="2ahUKEwjn6Zqht5eUAxX29zgGHS82FMYQ3ewLegQIDBAW" aria-label="Translated text: This research is motivated by the importance of the effectiveness of the allocation of the Regional Revenue and Expenditure Budget (APBD) as a fiscal policy instrument in improving community welfare at the regional level, especially in Sidoarjo Regency which has a relatively large fiscal capacity but requires evaluation of the impact of budget allocation. This study aims to analyze the effect of APBD allocation on community welfare and identify priority spending sectors that contribute to improving the quality of life. The research method uses a mixed method approach with an explanatory sequential design. The quantitative sample consists of 15 community respondents selected using a stratified random sampling technique based on sub-district areas. Meanwhile, qualitative informants consist of 5 regional apparatus officials and 5 academics. Data analysis was carried out using multiple linear regression and thematic analysis integrated through triangulation. The results of the study indicate that budget allocations in the education, health, infrastructure, economic empowerment, and social protection sectors with a high level of realization contribute significantly to increasing access to public services, expanding employment opportunities, and strengthening community economic activities. In conclusion, targeted, effective, and accountable APBD management is an important factor in improving community welfare, while providing theoretical contributions to regional public finance studies and practical implications for regional governments in formulating budget allocation policies based on sustainable development priorities.">Penelitian ini dilatarbelakangi oleh pentingnya efektivitas alokasi Anggaran Pendapatan dan Belanja Daerah (APBD) sebagai instrumen kebijakan fiskal dalam meningkatkan kesejahteraan masyarakat di tingkat daerah, khususnya di Kabupaten Sidoarjo yang memiliki kapasitas fiskal relatif besar namun memerlukan evaluasi terhadap dampak pengalokasian anggaran. Penelitian ini bertujuan menganalisis pengaruh alokasi APBD terhadap kesejahteraan masyarakat serta mengidentifikasi sektor prioritas belanja yang berkontribusi terhadap peningkatan kualitas hidup. Metode penelitian menggunakan pendekatan mixed method dengan desain explanatory sequential, Sampel kuantitatif terdiri dari 15 responden masyarakat yang dipilih menggunakan teknik stratified random sampling berdasarkan wilayah kecamatan. Sementara itu, informan kualitatif terdiri dari 5 orang pejabat perangkat daerah dan 5 akademisi. Analisis data dilakukan dengan regresi linear berganda dan analisis tematik yang diintegrasikan melalui triangulasi. Hasil penelitian menunjukkan bahwa alokasi anggaran pada sektor pendidikan, kesehatan, infrastruktur, pemberdayaan ekonomi, dan perlindungan sosial dengan tingkat realisasi yang tinggi berkontribusi signifikan terhadap peningkatan akses layanan publik, perluasan kesempatan kerja, serta penguatan aktivitas ekonomi masyarakat. Kesimpulannya, pengelolaan APBD yang terarah, efektif, dan akuntabel menjadi faktor penting dalam meningkatkan kesejahteraan masyarakat, sekaligus memberikan kontribusi teoretis pada kajian keuangan publik daerah dan implikasi praktis bagi pemerintah daerah dalam merumuskan kebijakan alokasi anggaran berbasis prioritas pembangunan yang berkelanjutan.